International science and technology cooperation oriented to research universities - Chuong, Le Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Research university is a novel concept in education and training activities in Vietnam. Many universities are searching to build the contents and road maps which would lead them to research universities. In the world actually, research universities become largely extended categories to attract students to enroll. One of the success factors of research universities is international science and technology cooperation which would be figured in the contents for building research universities Code: 14091701